Design and Development of in-motion Inflator - Zainol Rashid B. Hj. Osman, Zainol Rashid (Universiti Teknologi Petronas, 2009)
This report contains the final prototype working principal and result gained from the experiment for the final year project, which is The Design and Development of In-Motion Tyre Inflator. The objective of the project is to design and fabricate a tyre inflator which can control the pressure of air inside the tyre while the vehicle is moving. The final result and analysis shown that the project is a success but can be modified for future improvement. The challenge in this project is to design the rotary joint or seal bearing that will act as the connectors between the tubes of the tyre to the compressor. The design of the system and the test rig are completed and all the technical drawing done by AutoCAD software. The system comprises of an external compressor that will transfer air to the under inflated tyre via a rotary joint that have been designed. The rotary joint can effectively be the medium for air transfer and avoid hose tangling during the transfer. The relationship between the air pressure and the tyre width are demonstrated by the relationship of pressure with the tyre footprints. The pressure range used for the experiment is 26 psi until 32 psi. The rotary joint was also tested to rotate at 25 Rpm for three minutes in order to detect any air leakage at 28 psi.